Effect of Mobility and Different Data Traffic in Wireless Ad Hoc Network (International Journal of Scientific Research and Management (IJSRM), 2015)
An Ad-Hoc Network is a self-configuring network of mobile nodes connected by wireless links, to form an arbitrary topology. In this paper, we have studied the effects of various mobility models on the performance of three routing protocols AODV,OLSR and ZRP. For experiment purposes, we have considered four mobility scenarios: Random Waypoint, Group Mobility, Freeway and Manhattan models. These four Mobility Models are selected to represent possibility of practical application in future. Performance comparison has also been conducted across different data traffic. Experiment results illustrate that performance of the routing protocol varies across different mobility models.